Managerial Ownership, Company Size, and Profitability as Determinant Factors of Tax Avoidance in Food and Beverage Companies Listed on the IDX in 2020-2023 - Deni Rachmad Sulistiyanto; Heru Tjaraka (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study examines the effect of managerial ownership, company size, and profitability on tax avoidance in food and beverage companies listed on the Indonesia Stock Exchange for the period 2020-2023. The background of this study is based on the legal but controversial practice of tax avoidance, which has an impact on state revenues and company reputation. This study aims to analyze the relationship between these variables and the level of tax avoidance. The method used is multiple regression with panel data, involving 24 companies as samples selected through purposive sampling. Secondary data were obtained from the company's audited financial statements. The results of the study indicate that managerial ownership has a significant negative effect on tax avoidance, indicating that the greater the managerial ownership, the lower the level of tax avoidance. Conversely, company size does not show a significant effect on tax avoidance. Profitability significantly affects tax avoidance, where more profitable companies tend to implement more complex tax avoidance strategies. This study makes an important contribution to the tax avoidance literature, providing insight for policymakers to formulate more effective regulations and assisting companies in managing tax strategies efficiently.